Virtual Trial And Monte Carlo Analysis Of Model-Based Glycaemic Control Protocol With Reduced Nursing Effort - Athirah, Razak; Normy Norfiza, A. Razak; Nurhamim, Ahamad; Fatanah, Suhaimi; Ummu Kulthum, Jamaludin (Penerbit Universiti Teknologi Malaysia, 2015)
Tight glycaemic management has been shown to be beneficial to the outcomes of patients receiving intensive care. However, tight glycaemic control (TGC) protocol within intensive care (ICU) comes with a high clinical demand, namely high nursing effort. Thus, there is a need for a protocol that is safe, effective, robust, yet does not require a high nursing effort. A less intensive protocol is designed to use a combination of subcutaneous long-acting insulin (glargine) with IV insulin bolus and only requires blood glucose (BG) measurements every 4 hours while maintaining measurement within 4.0-6.1 mmol/L.